Improve Students' English Vocabulary Using the Smart TTS game App - Nasrum, MultikaSari; Sari, Puspa; Nasriandi, Nasriandi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
In learning foreign languages, especially English, students often need help with several obstacles, including requiring more vocabulary mastery. This research aims to improve students' vocabulary using the Smart TTS game application. The research method used in this study is quasi-experimental. The data processing results show that this application effectively improves students' vocabulary